The impact of iatrogenic complications in oral surgery for the brain diseases’ diagnosis – a case report - Białkowska-Głowacka, Jolanta; Rychlewska, Kamila; Więcek, Karol; Janas-Naze, Anna (Journal of Education, Health and Sport, 2017)
The article presents a case of a patient, who underwent a lower third molar surgery, resulting a retained metal foreign body in mandible, which in turn caused numerous artifacts in the MRI of the brain and resulted in its false interpretation.